Pengembangan Video Animasi untuk Meningkatkan Minat Siswa Mengenal Sejarah Islam - Awalfuady, Muhamad Dede Aufa; Nurjanah, Hifni Fitriah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze Generation Z's digital communication strategies through linguistic creativity in comments on the TikTok platform from a pragmatic perspective. The method used is a descriptive qualitative approach with pragmatic analysis. The research data was obtained from comments on a number of popular accounts that are widely accessed by Generation Z. The results of the study show that linguistic creativity functions as a pragmatic strategy that supports communication efficiency, affirms group identity, and strengthens social relationships between users. Furthermore, the use of language with a sense of solidarity shows that digital communication not only functions as a means of information exchange but also as an instrument for forming social closeness and self-expression. Thus, this study confirms that Generation Z's digital communication on TikTok plays an important role in shaping identity, social networks, and contemporary language culture.